Social Diversity on Corporate Boards in a Country Torn by Civil War - Nazliben, Kamil K.; Renneboog, Luc; Uduwalage, Emil (Journal of business ethics, 2024)
We examine how social diversity and inclusiveness on corporate boards affect corporate performance and monitoring in Sri Lanka, a country subject to decades of polarization, civil war, and even genocide. Barely more than a decade after the civil war, we find that board social diversity on the basis of ethnicity, religion, language, gender, and nationality of the board members is positively related to corporate performance, both in terms of stock market performance and accounting returns, and to corporate financial stability. The main positive effects of social diversity derive from ethno-linguistic inclusiveness. The results are confirmed by an instrumental variable approach that addresses endogeneity issues. We find no evidence that inter-personal and moral conflicts or communication problems among board members negatively affect firm performance.